MELALUI KKN TEMATIK COVID – 19 UNIBA TAHUN 2020 MEMBUDAYAKAN HIDUP SEHAT DI ERA NEW NORMAL SEBAGAI UPAYA MELAWAN COVID-19 - Sudarwati Sudarwati (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2020)
In 2020, the implementation of the KKN at the Islamic Batik Surakarta University in 2020 has a covid-19 situation that has hit the world. The work program carried out by KKN is adjusted to what is currently happening, the program is to support the government in breaking the Covid-19 chain, most importantly educating the public about the dangers of Covid-19 and living a new life in the new normal era. Especially in Saren Village, Klijambe District, Sragen Regency. Activities that support breaking the Covid-19 chain include sharing masks, hand hygiene kits, cleaning mosques, jogo tonggo and socializing about the dangers of Covid, signs of Covid and how to protect yourself from Covid. In addition to activities to break the chain of Covid -19 KKN, UNIBA Surakarta held activities to support the education sector in Saren Village, Kalijambe, Sragen such as building libraries and teaching TPA. Keywords: KKN UNIBA Surakarta, Saren Village, Kalijambe, Sragen.